2020
DOI: 10.1159/000511993
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Status in a Cancer Patient Population from Franconia, Germany

Abstract: <b><i>Background:</i></b> Vitamin D has been shown to be associated with reduced risk and severity of COVID-19 and exerts regulating effects on all hallmarks of cancer. The goal of this study was to analyze the vitamin D status of a cancer patient cohort from our clinic in the Franconian region, Germany. <b><i>Methods:</i></b> 25-hydroxyvitamin D concentrations were available for 116 patients included in prospective trials in our clinic. Associations of vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…So far, this phenomenon remains enigmatic. The observed inverse relationship between platelet count and 25(OH)D in the NAKO subcohort is consistent with the results from studies that found a higher vitamin D status associated with a lower platelet count [ 44 , 45 , 47 ]. However, antithrombotic effects of the vitamin D-vitamin D receptor axis have already been described [ 48 ] and indicate an important role of vitamin D in antithrombotic homeostasis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…So far, this phenomenon remains enigmatic. The observed inverse relationship between platelet count and 25(OH)D in the NAKO subcohort is consistent with the results from studies that found a higher vitamin D status associated with a lower platelet count [ 44 , 45 , 47 ]. However, antithrombotic effects of the vitamin D-vitamin D receptor axis have already been described [ 48 ] and indicate an important role of vitamin D in antithrombotic homeostasis.…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly, individuals with better vitamin D status were more likely to have low erythrocyte count, hemoglobin, hematocrit, thrombocyte count, and leukocyte count. However, a negative association between vitamin D status and hematological parameters, including leukocyte count, was also found in other human studies [ 42 45 ], although other trials found no relationship [ 46 ]. So far, this phenomenon remains enigmatic.…”
Section: Discussionmentioning
confidence: 60%
“…In French adults in an urban setting, lack of sunlight exposure and relatively low dietary intake of vitamin D require attention owing to the prevalence of vitamin D deficiency in that community 20 . Klement et al 21 suggested that low vitamin D in cancer patients can be enhanced with proper exposure to the sunlight and intake of supplements. They investigated the levels of calcifediol with blood counts and some anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%